2022
DOI: 10.3390/jpm12091374
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obstetric Complications and Intravitreal Anti-Vascular Endothelial Growth Factor Agents or Intravitreal Corticosteroids

Abstract: This nationwide population-based cohort study aimed to describe the use of intravitreal injections (IVTs) of anti-vascular endothelial growth factor (anti-VEGF) agents and corticosteroids in pregnant women in France and to report on the incidence of obstetric and neonatal complications. All pregnant women in France who received any anti-VEGF or corticosteroid IVT during pregnancy or in the month preceding pregnancy from 1 January 2009 to 31 December 2018 were identified in the national medico-administrative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
5
0
3
Order By: Relevance
“…Fetal lesions or fetal distress was reported in 11 (17.7%) cases receiving anti-VEGF agents vs. four (12.5%) receiving CS. Multivariant analysis showed that anti-VEGF agents were not associated with a higher risk of obstetric and neonatal complications when compared with CS [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal lesions or fetal distress was reported in 11 (17.7%) cases receiving anti-VEGF agents vs. four (12.5%) receiving CS. Multivariant analysis showed that anti-VEGF agents were not associated with a higher risk of obstetric and neonatal complications when compared with CS [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory to this proposed association is the prevalence of an already high miscarriage rate (30-40%) among otherwise healthy females. Others have reported uneventful pregnancies with no developmental defects after IVT anti-VEGF administration in pregnancy, though long-term follow-up data is currently not available [ 4 , 9 ]. Administration of IVT anti-VEGF during the embryogenic phase in an otherwise undiagnosed pregnancy has also shown variable results [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eine Studie von Ben Ghezala et al [9] ist die größte Zusammenfassung solcher Fallberichte aus Frankreich. Die Arbeit berichtet von 228 intravitrealen Anti-VEGF- oder KS-Injektionen bei 139 Patientinnen entweder während der Schwangerschaft oder im Monat vor der Schwangerschaft: 93 Frauen erhielten nur den Anti-VEGF-Wirkstoff, 39 erhielten nur das KS und 7 erhielten beides.…”
Section: Diskussionunclassified
“…Fötale Läsionen oder fötaler Stress wurden bei 11 der Frauen (17,7%), die eine Anti-VEGF-Injektion erhielten, berichtet, während dies bei 4 Frauen (12,5%) der Fall war, die eine KS-Injektion erhielten. Die multivariate Analyse zeigte, dass die Anti-VEGF-Wirkstoffe im Vergleich zu KS nicht mit einem höheren Risiko für obstetrische oder neonatale Komplikationen in Zusammenhang stehen [9].…”
Section: Diskussionunclassified
See 1 more Smart Citation